Isolation and characterization of rabbit periosteum-derived mesenchymal stem cells - Surumbayeva, A.; Ogay, Vyacheslav (National Laboratory Astana, NAZARBAYEV UNIVERSITY, 2016)
Periosteum represents a good source for mesenchymal stem cells (MSCs). They have been regarded as a promising therapeutic tool for muscoskeletal regeneration. Periosteum-derived MSCs have higher osteogenic potential in vitro than MSCs from other tissues and organs. The aim of this study was to isolate and characterize rabbit periosteumderived MSCs for further their application for bone tissue engineering
Keywords: periosteum; mesenchymal stem cells; regenerative medicine; rabbit